2017
DOI: 10.21660/2017.39.41553
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Infrared Remote Sensing of Hydrocarbon in Lagos- Southern Nigeria: Application of the Thermographic Model

Abstract: ABSTRACT:The paper presents a technique for investigating remote sensing imagery to explore hydrocarbon sites, oil traps and spills. This research adopts a model approach to oil exploration against conventional or traditional methods. The model used here is the Environmental Thermographic Model (ETM). Key parameters such as surface emissivity, surface temperature, long wave radiation and geological mapping which constitute the model were used alongside data generated from the Moderate Resolution Imaging Spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The thermal remote sensing is based on the infrared portion of the spectrum, and measures the emitted thermal energy [8]. This, thermal remote sensing is kind of passive remote sensing, since it discover natural emitted radiation.…”
Section: Thermal Remote Sensingmentioning
confidence: 99%
See 3 more Smart Citations
“…The thermal remote sensing is based on the infrared portion of the spectrum, and measures the emitted thermal energy [8]. This, thermal remote sensing is kind of passive remote sensing, since it discover natural emitted radiation.…”
Section: Thermal Remote Sensingmentioning
confidence: 99%
“…Then, the integration of vegetation indices from remotely sensed images with other hydro meteorological data is extensively used for monitoring natural hazards for instance the droughts. As far as calculate emissivity are concerned, the emissivity of the material surface is the emitting energy efficiency as thermal radiation [8]. Whereas, the thermal radiation is electromagnetic radiation, and it could include both visible (light), and infrared radiation [21], which is invisible to human being eyes.…”
Section: Thermal Remote Sensingmentioning
confidence: 99%
See 2 more Smart Citations
“…The best example is International set of aerosol measurements «AERONET» , containing more than 500 automated stations for measurements of atmospheric aerosol optical depth at the wavelengths 340, 440, 500, 670, 870, 1020 nm [2]. Other example for joint measurements is remote measurements of soil pollution carried out in ultraviolet, visible and infrared bands [3,4], and also the method for detection of hydrocarbons fire in ultraviolet and infrared bands [5]. Thus it may be concluded that joint multispectral measurements are inseparable part of theory and practice of multispectral measurements and optimization of them is an actual task.…”
Section: Introductionmentioning
confidence: 99%